10 fallacies about Subtitling for the d/Deaf and the hard of hearing - Neves, Josélia (The Journal of Specialised Translation, 2008)
Even though subtitling for the d/Deaf and the hard of hearing is now an established audiovisual translation type, it is not yet fully understood, even by its stakeholders. Some of the misconceptions have led to unnecessary misunderstandings which could hinder progress. A better understanding of the social and technical constraints of this kind of subtitling may prove to be important at a time when technology is offering new opportunities. In this paper, a few of the above mentioned misconceptions will be addressed in a critical eye and a provocative tone. Ten fallacies are listed in the hope that other researchers and professionals might take up the problematic issues as a starting point for further research and thus shed further light on them.